Rancang Bangun Alat Monitoring Suhu Blood Bank Refrigerator Dengan Sistem Database - Alian Jerly Soeparli; Muhtar Muhtar; Lili Ruhyana; Gunawan Gunawan (Jurnal Tika, 2023)
Blood Bank Refrigerator is a piece of equipment used as a cooler. It is usually used to store blood, and various blood products such as plasma, platelets, and red blood cells. Blood Bank Refrigerator can maintain the quality of blood products even if stored for a long time. Inappropriate temperatures can make blood clot or rupture, making it unsafe to give to patients. The problem with the blood bank referigator is that it cannot be monitored, and currently monitoring the temperature in the blood storage refrigerator is still done independently by taking manual notes.Based on the description above, in this Final Project the author will make a database-based blood bank referigator temperature monitoring tool. This research uses the System Development Life Cycle (SDLC) method, which is the process of making and changing systems as well as models and methodologies used to develop a system. The temperature measurement is done with a value of 4 ° C which is displayed on the LCD and database. Using an average time of 12 minutes and measurements every 2 minutes testing 6 times from 2 blood bank refrgator obtained an average difference of less than 0.2°C. After testing and data collection of the module, it can be concluded that the module and program run well in accordance with the plan.